Effect of Probiotic and Exogenous Fibrolytic Enzyme Treated Rice Straw on the Performance of Hariana Heifers - A.Patel, V. Kumar; M. Kumar; R. Kushwaha; S. Vaswani; A. Kumar (Indian Journal of Animal Nutrition, 2024)
This study was conducted to evaluate the probiotic and exogenous fibrolytic enzyme treated rice straw on the performance of Heifers. Eighteen heifers were selected and allocated into three groups having six animals in each and fed treatment diet for 120 days. The control group was fed on basal diet whereas, group-1 was supplemented basal diet with 5g/kg probiotic (Saccharomyces cerevisiae) and group-2 was supplemented basal diet with 7g/kg exogenous fibrolytic enzymes (EFE). The nutrient requirements of heifers were met by feeding concentrate mixture, Jowar, and paddy straw (50:30:20 ratio) on DM basis. No effect on DMI, FCR, FCE but body weight gain was found significantly higher (P